Utilizing Japanese Community Engagement: Understanding Malaysian Traditional Music Therapy for Children with Special Needs - Ahmad, Noorlila; Abu Bakar, Abu Yazid (JAPANEDU: Jurnal Pendidikan dan Pengajaran Bahasa Jepang, 2023)
This study suggests an intervention treatment relating to the dances and songs of “Dikir Barat” and “Kuda Kepang” and utilizes the distinctive methods of Malay traditional performance. Children with specific difficulties will benefit from the therapy’s emphasis on audience perception skills and socialization. The audience for this study, which comprised students and people with special needs, was polled using a survey questionnaire that was provided as part of a special concert. The descriptive analysis of the 5-point Likert scale survey’s 20 items yielded the proportion of each item.  As a result, it has been found that shows, particularly those that incorporate the performing arts of singing, dancing, and acting, greatly affect and have an impact on groups with special needs. This study adds to the body of knowledge by demonstrating how conventional music therapy can encourage children with special needs to become more actively involved in their own lives as well as that of their community.